The American Army in Germany, 1918-1923 : success against the odds - Nowowiejski, Dean A., 1956- 1956- (Modern war studies, 2021)
"After the collapse of the German Imperial Army in 1918, several armies, including the British and French, occupied the German Rhineland as part of the provision of the Treaty of Versailles. The US Army occupied the central area along the Mosel River. As Dean Nowowiejski asserts in Success against the Odds, the US Occupation is a little-known success story; it's a story he tells in this book. Nowowiejski begins by analyzing the march into Germany and the activities of the United States Third Army, the Army of Occupation from 1918 to mid-1919. He studies the performance of American military governor Major General Henry T. Allen and the creation of the American Forces in Germany (AFG), the enduring force from 1919-1923, emphasizing the training of the force and the everyday life of the soldier during the occupation. He concludes by demonstrating that the American occupation of the Rhineland is a case study of successful military government enabled by competent military force, and asserts that the occupation had greater potential impact in military and diplomatic terms than previously realized"